Progressive Hypertrophic Genital Herpes in an HIV-Infected Woman despite Immune Recovery on Antiretroviral Therapy - Mark H. Yudin; Rupert Kaul (Hindawi Limited, 2008)
Most HIV-infected individuals are coinfected by Herpes simplex virus type 2 (HSV-2). HSV-2 reactivates more frequently in HIV-coinfected individuals with advanced immunosuppression, and may have very unusual clinical presentations, including hypertrophic genital lesions. We report the case of a progressive, hypertrophic HSV-2 lesion in an HIV-coinfected woman, despite near-complete immune restoration on antiretroviral therapy for up to three years. In this case, there was prompt response to topical imiquimod. The immunopathogenesis and clinical presentation of HSV-2 disease in HIV-coinfected individuals are reviewed, with a focus on potential mechanisms for persistent disease despite apparent immune reconstitution. HIV-infected individuals and their care providers should be aware that HSV-2 may cause atypical disease even in the context of near-comlpete immune reconstitution on HAART.